Dampak Program Kampung Sehat Terhadap PHBS Anak Usia Dini di Masa Pandemi - Ahmad Sanusi; Naimah Naimah (AWLADY : Jurnal Pendidikan Anak, 2022)
Since the beginning of 2020 the Covid-19 virus has spread to Indonesia and has caused thousands of children to be infected with the virus in various regions, one of which is the province of NTB. Various steps have been taken by the government in preventing the transmission of covid 19 in NTB, one of the steps that the NTB government has initiated is the healthy village program. The implementation of the healthy village program in NTB is carried out with a competition procedure which is followed by all villages throughout NTB, one of the villages is Pejanggik village. Therefore the aim of the research in this article is to determine the impact of the village health program on the improvement of clean and healthy living habits (PHBS) for early childhood during the pandemic in Bir'ali hamlet, Pejanggik village, Praya Tengah district, Central Lombok district. This type of research uses quantitative research with primary data sources. The type of data collection was in the form of a questionnaire or koesioer distributed to 38 respondents, namely parents of early usa children in Bir'ali hamlet, Pejanggik village, Praya Tengah district, Central Lombok district. While the data analysis technique used the instrument feasibility test in the form of validity and reliability tests. In addition, this analysis technique also uses multiple linear regression tests. Based on the research results, it shows that the research instrument can be declared valid and reliable. From the results of the t test the impact of the village health program had a positive and significant impact on improving the clean and healthy lifestyle (PHBS) of early childhood in Bir'ali hamlet, Pejanggik village, Central Praya district, Central Lobik district. From the variable contribution, the village health program was able to explain the PHBS variable for early childhood by 27%.